ОСОБЛИВОСТІ ПЕДАГОГІЧНОГО БАЧЕННЯ ФЕОКТИСТОМ ХАРТАХАЄМ ПРОЦЕСУ ВИКЛАДАННЯ МОВ В ПОЛЬСЬКИХ ГІМНАЗІЯХ ДРУГОЇ ПОЛ. ХІХ СТ. (Педагогіка вищої та середньої школи, 2007)
The language teaching methodology can be defined as the comparative methodology based on synthetic means taking into account perceptual psychology, teaching approach in native language, linguistic translating, mechanical and intentional reading.